Chemical Antioxidant Activity of Thunbergia Lauriforia Linn. (Rang Chuet) Leaves and its Combined Extracts - สุนทรารักษ์ ฉัตรทิพย์; Oonsivilai, Ratchadaporn (Food and Applied Bioscience Journal, 2022)
Plant extracts and various natural products may exhibit a synergistic interaction. Thunbergia laurifolia Lindl., also known as "Rang Chuet" in Thailand, is a plant with antioxidant properties widely used in traditional medicine. Zingiber officinale (ginger), a flavoring ingredient in foods, is well known for its numerous health benefits. There have been no studies on the interaction of antioxidant activity of Rang Chuet with other plant extracts up until now. Thus, this study aimed to investigate the interaction of Rang Chuet water extract (RWE) and ginger ethanol extract (GEE). First, the total phenolic content (TPC) and total flavonoid content (TFC) of RWE and GEE were determined. High-performance liquid chromatography spectrometry (HPLC) was used to examine the phytochemical profile of RWE. The RWE represented coumaric, caffeic, protocatechuic, rosmarinic, and gallic acid as phenolic compounds and apigenin as flavonoids. Chemical antioxidant assays were performed on single and combined extracts using the ABTS·+ radical cation scavenging capacity assay (ABTS), DPPH free radical scavenging capacity assay (DPPH), ferric reducing antioxidant power assay (FRAP), and ferric chelating assay (FIC). A substantial body of research demonstrated that the combined extracts of RWE and GEE had an additive interaction in various antioxidant assays. Furthermore, a 5:1 v/v ratio of RWE and GEE demonstrated a synergistic effect in DPPH and FRAP assays. The synergistic ratio could be used to create nutraceutical formulations or various food products with antioxidant activity to prevent oxidative diseases.